Platelet rich plasma: Effective treatment for repairing of spinal cord injury in rat - Reza Salarinia; Hamid Reza Sadeghnia; Daryoush Hamidi Alamdari; Seyed Javad Hoseini; Asghar Mafinezhad; Mahmoud Hosseini (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of the present study was to evaluate the effect of PRP on the repair of spinal cord injury in rat model. Material and methods: Rats were randomly divided into three groups with six rats in each group. Then, spinal cord injury was performed under general anesthesia using “weight dropping” method. Control group included rats receiving normal saline, group two received PRP 1 week after injury; group three received PRP 24 h after injury. The motor function was assessed weekly using the Basso, Beattie, and Bresnahan (BBB) locomotor rating scale. Anterograde tracing was performed for evaluation of axon regeneration. Result: Motor recovery was significantly better in the rats treated with PRP 24 h after injury than the control group. In the rats treated with PRP 1 week after injury and rats treated with PRP 24 h after injury, the average numbers of BDA-labeled axons were statistically different from the control group. Conclusion: Our experimental study demonstrated positive effects of platelet rich plasma on nerve regeneration after spinal cord injury. Keywords: Spinal cord injury, Platelet rich plasma, Locomotor function